PERUBAHAN MATA PENCAHARIAN SUKU AKIT DI DESA KEMBUNG BARU KECAMATAN BANTAN KABUPATEN BENGKALIS - kki Kurnia Sari; Swis Tantoro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Akit Tribes who are in Kembung Baru village precisely located in Dusun AkitJaya has moved from the former they live on the shoreline and estuary of theriver, has now moved to life by rising land area. This study aims to determine theprocess of livelihoods change of Akit from fishermen to non-fishermen inKembung Baru Village, Bantan District of Bengkalis and factors of change oflivelihood of Akit from fishermen to non-fishermen in Kembung Baru Village,Bantan District, Bengkalis. This research uses descriptive quantitative methodand research sample or respondent of this research is 100 head of family fromAkit Tribe in Kembung Baru Village, District of Bengkalis Regency. Samplingmethod with saturated sampling (census). Data collection tool that is in the formof observation and questionnaire which contains the question of the planninginterview addressed to the respondent. Data analysis techniques use thepercentage formula of each questionnaire question category. The process ofchanging the livelihood of the Akit Tribe starts from the process of moving theirshelter from the coast to the mainland, resulting in adjustment of work in the landarea so that they change livelihood from fishermen to non-fishermen. Factors thataffect the external factors that come from outside circumstances such as: becauseof the increasingly difficult life of the sea, the high risk of working at sea, thechange in income when it is changing livelihood.Keywords: Fisherman, Livelihood, Non-fisherman, Tribe Akit